Comparing positron emission tomography imaging and cerebrospinal fluid measurements of β-amyloid - Landau, Susan M.; Lu, Ming; Joshi, Abhinay D.; Pontecorvo, Michael; Mintun, Mark A.; Trojanowski, John Q.; Shaw, Leslie M.; Jagust, William J. (Annals of neurology, 2013)
Objective We examined agreement and disagreement between 2 biomarkers of β‐amyloid (Aβ) deposition (amyloid positron emission tomography [PET] and cerebrospinal fluid [CSF] Aβ1–42) in normal aging and dementia in a large multicenter study. Methods Concurrently acquired florbetapir PET and CSF Aβ were measured in cognitively normal, mild cognitive impairment (MCI), and Alzheimer's disease participants (n = 374) from the Alzheimer's Disease Neuroimaging Initiative. We also compared Aβ measurements in a separate group with serial CSF measurements over 3.1 ± 0.8 years that preceded a single florbetapir session. Additional biomarker and cognitive data allowed us to further examine profiles of discordant cases. Results Florbetapir and CSF Aβ were inversely correlated across all diagnostic groups, and dichotomous measurements were in agreement in 86% of subjects. Among subjects showing the most disagreement, the 2 discordant groups had different profiles: the florbetapir+/CSF Aβ− group was larger (n = 13) and was made up of only normal and early MCI subjects, whereas the florbetapir−/CSF Aβ+ group was smaller (n = 7) and had poorer cognitive function and higher CSF tau, but no ApoE4 carriers. In the longitudinal sample, we observed both stable longitudinal CSF Aβ trajectories and those actively transitioning from normal to abnormal, but the final CSF Aβ measurements were in good agreement with florbetapir cortical retention. Interpretation CSF and amyloid PET measurements of Aβ were consistent in the majority of subjects in the cross‐sectional and longitudinal populations. Based on our analysis of discordant subjects, the available evidence did not show that CSF Aβ regularly becomes abnormal prior to fibrillar Aβ accumulation early in the course of disease. Ann Neurol 2013;74:826–836